Landscape Design: Twenty-Two Ideas for a Low-Care, Low-Cost Landscape - Gail Hansen (EDIS)
Many homeowners desire a beautiful landscape but are often discouraged by the lack of time and money needed to create and care for the garden of their dreams. A pleasing, low-care, low-cost landscape is possible, however, with careful planning, appropriate plant choices, and a thoughtful design. This 11-page fact sheet was written by Gail Hansen and published by the UF Department of Environmental Horticulture, April 2011.